THE COMPARISON OF FERTILIZING CAPACITY OF NATIVE AND NEW HAMPSHIRE MALE CHICKENS - S.M. Thiab , R.; J. Mahdi, T. (The Iraqi Journal of Veterinary Medicine, 1987)
This experiment was conducted to compare and estimate the fertilizing capacity of native with New Hampshire chicken semen. Also to study the effect. Of different levels of semen dosage on fertility percentage, duration’ of fertility and duration of fertilizing ability. In this experiment (12) native and (12) N.H. male chicken with (240) Hisex laying hens have been used. The results of the statistical analysis showed that there were no significant (P>0.05) differences between the native and N.H. male chickens for the fertilizing capacity. fertilizing percentage in duration of fertility and fertility duration. The values were 90.40, 90.73%; 85.77, 85.60%; 12.11, 12.3 days for native and N.H. chickens, respectively. There were no significant (P>0.05) effect of increasing semen concentration (100, 200, 300 million sperm) per single insemenation on the percentage of fertilization and duration of fertility percentage. The values for percentage of fertilization, duration of fertility percentage and fertility duration were 89.76%, 91.79, 90.14; 85.33%, 88.72, 83.01; 12.24, 11.90, 12.50 days, respectively. Using the above mentioned concentration levels, no significant interaction was found between semen concentration and male groups.